2001
DOI: 10.1074/jbc.m102344200
|View full text |Cite
|
Sign up to set email alerts
|

Human Glutathione Transferase P1-1 and Nitric Oxide Carriers

Abstract: S-Nitrosoglutathione and the dinitrosyl-diglutathionyl iron complex are involved in the storage and transport of NO in biological systems. Their interactions with the human glutathione transferase P1-1 may reveal an additional physiological role for this enzyme. In the absence of GSH, S-nitrosoglutathione causes rapid and stable S-nitrosylation of both the Cys(47) and Cys(101) residues. Ion spray ionization-mass spectrometry ruled out the possibility of S-glutathionylation and confirms the occurrence of a poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
105
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 62 publications
5
105
1
Order By: Relevance
“…S-Nitrosation stoichiometry was determined by UV-difference spectroscopy as described in Ref. 22 based on an S-NO extinction coefficient of 750 M ÏȘ1 cm ÏȘ1 at 330 nm. Synthesis of GSNO and CysNO-GSNO and CysNO were synthesized as described previously (25) and frozen in aliquots at ÏȘ80°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…S-Nitrosation stoichiometry was determined by UV-difference spectroscopy as described in Ref. 22 based on an S-NO extinction coefficient of 750 M ÏȘ1 cm ÏȘ1 at 330 nm. Synthesis of GSNO and CysNO-GSNO and CysNO were synthesized as described previously (25) and frozen in aliquots at ÏȘ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Tryptophan Fluorescence-GSTP1-1 S-nitrosated at cysteines 47 and 101 has previously been discovered in vivo (19 -21) and produced in vitro (22,23) by reaction with GSNO. Here, we generated a series of cysteine mutants with the aim of examining the kinetics of nitrosation of GSTP1-1 in detail.…”
Section: Gstp1-1 S-nitrosation Probed Bymentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that GST may act as a nitric oxide carrier in some circumstances. 11 Decreased GSTM1 expression in stroke-prone spontaneously hypertensive rats 10 may reduce antioxidant defences. Resulting lower renal GSTM1 levels may lead to increased superoxide formation and reduced nitric oxide bioavailability in the renal medulla and cortex.…”
mentioning
confidence: 99%